Vanadium-doped indium tin oxide window layer in Sb2Se3 solar cell. (June 2022) - Lin, Yi-Cheng; Lin, Jun-Han; Hsu, Rui-Yun
Abstract: Antimony selenide (Sb2 Se3 ) is an emerging photovoltaic material. Indium tin oxide (ITO) is commonly used as the window layer material in Sb2 Se3 solar cells; however, ITO films have poor absorption in the near-infrared spectrum. Our objective in this research was to replace conventional ITO with vanadium-doped indium tin oxide (ITO:V) to improve the near-infrared light transmittance of Sb2 Se3 thin film solar cells and thereby enhance the efficiency of solar cells. The experiment parameters included vanadium doping concentration and annealing temperature. ITO films doped with 0.35 at.% V and annealed at 100 °C for 30 min outperformed conventional ITO films in terms of photovoltaic performance. The proposed scheme improved light transmittance from 80.03% to 83.02% over a wavelength range of 400–1100 nm, which led to a significant improvement in Jsc and device efficiency (from 4.5% to 5.6%). It appears that ITO films can be doped with vanadium to improve transmittance by reducing refractive index degradation in the near-infrared region. Highlights: Vanadium-doped indium tin oxide (ITO:V) window layer in Sb2 Se3 solar cell was studied. ITO with 0.35 at.%V doping and annealing at 100 °C for 30 min demonstrated excellent photoelectric properties. Sb2 Se3 solar cell presented improvements device efficiency from 4.5% to 5.6%. ITO with 0.35 at.%V doping can increase the transmittance in the near-infrared region.